2014
DOI: 10.1093/jnci/dju239
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of [131I] Metuximab in Treatment of Hepatocellular Carcinoma After Percutaneous Radiofrequency Ablation

Abstract: To assess the efficacy of combining radioimmunoconjugate [(131)I] metuximab with radiofrequency ablation (RFA) in hepatocellular carcinoma (HCC) treatment compared with RFA alone, a single-center randomized controlled trial was conducted on 127 patients with Barcelona Clinic Liver Cancer staging system (BCLC) classifications of 0-B stage. Patients received either RFA followed by [(131)I] metuximab (n = 62) or RFA alone (n = 65). The primary outcome was overall tumor recurrence. Statistical tests were two-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 16 publications
0
59
0
Order By: Relevance
“…S20060064). In a series of clinical trials, the injection of Licartin combined with transcatheter arterial chemoembolization , liver transplantation , or radiofrequency ablation in the treatment of HCC exhibits improved clinical efficacy. In this study, after treating SMMC‐7721‐CD147‐GFP cells with HAb18, the expression level of CD147ICD‐EGFP was decreased in a dose‐dependent manner (see supplementary material, Figure S7A), indicating HAb18 could inhibit γ‐secretase cleavage of CD147 and is an important mechanism by which HAb18 inhibits tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S20060064). In a series of clinical trials, the injection of Licartin combined with transcatheter arterial chemoembolization , liver transplantation , or radiofrequency ablation in the treatment of HCC exhibits improved clinical efficacy. In this study, after treating SMMC‐7721‐CD147‐GFP cells with HAb18, the expression level of CD147ICD‐EGFP was decreased in a dose‐dependent manner (see supplementary material, Figure S7A), indicating HAb18 could inhibit γ‐secretase cleavage of CD147 and is an important mechanism by which HAb18 inhibits tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer includes intrahepatic cholangiocarcinoma, human hepatocellular carcinoma (HCC) and other rare types, with HCC accounting for approximately 75–85% of all liver cancers . Currently, there are several drugs for HCC therapy, including antibody drugs, such as Opdivo (nivolumab) and Licartin ([ 131 I] metuximab injection; developed by our group ), and small‐molecule inhibitor drugs, such as sorafenib, regorafenib, and lenvatinib .…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy provided better local and intrahepatic tumor control and long-term survival (35). Bian et al reported that iodine-131 metuximab in treatment of HCC after RFA showed a greater anti-recurrence benefit than RFA monotherapy (36). Sorafenib, an oral multikinase inhibitor, has been proved as the firstline therapy method for patients with advanced HCC (37).…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…The molecular mechanisms underlying the acceleration effect of CD147 on HCC invasion and metastasis and the synergistic inhibition effect of I 131 ‐mab on HCC progression have been reported (Bian et al., ; Gou et al., ). Specifically, CD147 can activate the transforming growth factor‐β (TGF‐β) signaling pathway to promote the expression and secretion of MMPs in tumor cells and mesenchymal cells, which induces the epithelial–mesenchymal transition (EMT) in cancer cells and contributes to tumor invasion and metastasis (Ru, Wu, Chen, & Bian, ; Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms underlying the acceleration effect of CD147 on HCC invasion and metastasis and the synergistic inhibition effect of I 131 -mab on HCC progression have been reported (Bian et al, 2014;Gou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%